Penguatan Lembaga Adat Tuha Peut Dalam Penyelesaian Sengketa Di Kecamatan Sawang - Yulia Yulia; Faisal Faisal; Fauzah Nur Aksa (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Socialization and legal counseling on the Tuha Peut Traditional Institution in dispute resolution in Sawang District are part of community service activities. The background of this activity is that in the Qanun of Customary Institutions, Tuha Peut is one of the customary institutions that has the authority to settle disputes between members of a community of a village. In Sawang Subdistrict, Aceh Utara District, there are still many customary disputes that have not been resolved by customary settlement in the village and many have been reported by the community to the police. This is also due to the lack of knowledge of the Tuha Peut Customary Institution in resolving disputes at the village level. This socialization and legal counseling was carried out by presenting the material and continued with a discussion of questions and answers and swearing back. The results of socialization and legal counseling in Sawang District found that the results of the feedback provided by participants experienced an increase in understanding of the role of the Tuha Peut Traditional Institution in dispute resolution. The implementation of this activity received a good response from the Tuha Peut Customary Institution, because they increased their knowledge and they rarely got activities like this.